Changes of ATPase activity and lipid peroxidation in conditions of long-term hypokinesia - Shirvanyan, A. A.; Karapetyan, H. M.; Trchounian, A. H. (Հայաստանի ԳԱԱ «Գիտություն» հրատ.)
The aim of this work was to investigate the dynamics changes in mitochondrial ATPase’s activity and in lipid peroxidation in conditions of 30-day hypokinesia. It was shown that maximum lipid peroxidation level was observed in the kidneys and brain in the 20th day of stress, exceeding the norm by 20.87 % and 75.2 %, respectively. The maximum activity of Mg2+-dependent proton F0F1-ATPase of mitochondria was promoted in the liver of rabbit after 20-day of stressful effect by 48.8 % compared to unstressed animals. Thus, the analysis of the nature of changes in the lipid peroxidation processes and in the activity of mitochondrial ATPase can be the basis for identifying pathological processes caused by hypokinesia and for creating various means to prevent them. 30-օրյա հիպոկինեզիայի պայմաններում ուսումնասիրվել է միտոքոնդրիումային ԱԵՖազի ակտիվության և լիպիդների գերօքսիդացման գործընթացների փոփոխությունների օրինաչափությունների բնույթը: Ցույց է տրվել, որ լիպիդների գերօքսիդացման առավելագույն մակարդակ դիտվում է ճագարի երիկամներում և ուղեղում սթրեսի 20-օրյա ազդեցության դեպքում՝ նորման գերազանցելով համապատասխանաբար 20.87 % և 75.2 %-ով։ Միտոքոնդրիումային Mg2+ -կախյալ պրոտոնային F0F1-ԱԵՖազի ակտիվության առավելագույն խթանում բնականոն պայմանների համեմատությամբ դիտվում է սթրեսի ազդեցության 20-րդ օրը ճագարի լյարդում`48.8 %-ով։ Изучен характер изменений процессов перекисного окисления липидов и активности митохондриальной АТФазы в условиях 30-дневной гипокинезии. Показано, что максимальный уровень перекисного окисления липидов наблюдается в почках и в мозге при 20-дневном стрессе, превышая норму на 20,87 % и 75,2 % соответственно. Максимальная стимуляция активности Mg2+-зависимой митохондриальной F0F1-АТФазы по сравнению с нормой наблюдается в печени кролика на 48,8 %. Таким образом, анализ характера изменений процессов перекисного окисления липидов и активности митохондриальной АТФазы может служит основой для выявления патологических процессов, обусловленных гипокинезией, и создания в дальнейшем различных предотвращающих средств.
Keywords: Biochemistry; Biotechnology